Consenso mexicano para el diagnóstico y tratamiento de la dermatitis atópica en adolescentes y adultos - Rincón Pérez, Catalina; Larenas Linnemann, Désirée; Figueroa Morales, Marco Antonio; Luna Pech, Jorge A.; García Hidalgo, Linda; Macías Weinmann, Alejandra; Gómez Vera, Javier; Barba Gómez, José Fernando; Matta Campos, Juan José; Guevara Sangines, Esther; Jurado Santacruz, Fermín; López Tello Santillán, Adriana; et al. (2018)
Abstract Background: The diagnostic approaches and therapeutic strategies of atopic dermatitis (AD) are generally inconsistent among physicians and health institutions. Objective: To develop a consensus statement among experts to reduce the variations in practice regarding the diagnosis and treatment of patients ≥ 12 years with AD to improve their care. Methods: Systematic literature search in PubMed and GREAT. With methodological support and using the Delphi method, a formal consensus was developed among 16 experts in Dermatology and Allergology, based on the current evidence and its applicability in the Mexican context. Apart from intense electronic communication, several issues of disagreement were discussed in two face-to-face meetings. Results: The clinical experts reached consensus on 46 statements related to the definition, classification, diagnostic strategies and treatment of AD. For the diagnosis we suggest the Williams criteria and for severity scoring the SCORAD (by the doctor) and POEM (by the patient). In addition to general care and treatment education (workshops), we suggest four steps for treatment, depending on severity: 1. Topical treatment with anti-inflammatory agents (and systemic: antihistamines/antileukotrienes —low level evidence—) 2. Phototherapy, 3. Cyclosporin A and 4. Dupilumab, with the possibility of managing this biological earlier on if a fast effect is needed. In extrinsic AD we suggest evaluating the addition of allergen immunotherapy or an elimination diet, if there is an IgE-mediated respiratory or food allergy, respectively. Conclusion: The panel of experts reached consensus on relevant aspects of AD with a focus on the transcultural adaptation of recent evidence. Keywords: Atopic dermatitis; Atopic dermatitis treatment; Consensus; Cyclosporin A; Biological treatment; Dupilumab; Omalizumab.